Associations of lower-limb atherosclerosis and arteriosclerosis with cardiovascular risk factors and disease in older adults: The Atherosclerosis Risk in Communities (ARIC) study. (January 2022) - Stone, Keeron; Fryer, Simon; Faulkner, James; Meyer, Michelle L.; Heffernan, Kevin; Kucharska-Newton, Anna; Zieff, Gabriel; Paterson, Craig; Matsushita, Kunihiro; Hughes, Timothy M.; Tanaka, Hirofumi; Stoner, Lee
Abstract: Background & aims: Atherosclerosis and arteriosclerosis contribute to vascular aging and cardiovascular disease (CVD) risk. Both processes can be assessed simply in the lower-limbs and reflect systemic pathology. However, only atherosclerosis is routinely assessed, typically via ankle-brachial index (ABI). Arteriosclerosis can be assessed using femoral-ankle pulse wave velocity (faPWV), but no studies have identified whether ABI and faPWV similarly associate with overt CVD and risk factors, nor whether faPWV confers additional information. The aims of this study were to (i) compare associations of ABI and faPWV with traditional CVD risk factors, including age, sex, systolic blood pressure (SBP), high-density lipoprotein (HDL), total cholesterol (TC), smoking, and diabetes; and (ii) determine the independent and additive associations of ABI and faPWV with a composite measure of prevalent CVD. Methods: We evaluated ABI and faPWV in 4330 older-aged (75.3 ± 5.0 years) adults using an oscillometric screening device. Associations between ABI and faPWV with CVD risk factors and CVD were determined using mixed-model linear- and logistic-regression. Results: ABI and faPWV were associated with age, HDL, and smoking. ABI was associated with sex, TC, diabetes. faPWV was associated with SBP. Both ABI and faPWV were inversely associated with CVD. Low ABI (≤0.9 vs . >0.9) and low faPWV (≤9.94 vs . >9.94) increased the odds of CVD by 2.41-fold (95% CI:1.85, 3.17) and 1.46-fold (95% CI:1.23, 1.74), respectively. The inverse association between faPWV and CVD was independent of ABI and CVD risk factors. Conclusions: ABI and faPWV, measures of lower-limb atherosclerosis and arteriosclerosis, are independently associated with CVD risk factors and prevalent CVD. Assessment of faPWV may confer additional risk information beyond ABI. Graphical abstract: Image 1 Highlights: Ankle-brachial index (ABI) and femoral-ankle pulse wave velocity (faPWV) demonstrate unique associations with risk factors. Both ABI and faPWV are independently associated with cardiovascular disease. Low faPWV is associated with cardiovascular disease. Assessment of faPWV may confer unique and additive risk information beyond ABI.